An update on gastrointestinal disturbances in eating disorders. (1st November 2019) - Hetterich, Larissa; Mack, Isa; Giel, Katrin E.; Zipfel, Stephan; Stengel, Andreas
Abstract: Eating disorders, namely anorexia nervosa, bulimia nervosa and binge eating disorder are frequent diseases and often complicated by comorbidities, e.g. psychiatric or cardiovascular comorbidities. It is to note that also gastrointestinal symptoms/complications are frequently observed in patients with eating disorders. These diseases will be presented in the current review along with – where known – possible underlying mechanisms. Lastly, gaps in knowledge will be highlighted. Highlights: Eating disorders are often complicated by gastrointestinal symptoms/complications. Considerable overlap exists regarding symptoms and underlying comorbid diseases. Few gastrointestinal complications are exclusively observed in e.g. anorexia nervosa. Future studies are warranted to unravel underlying mechanisms.